Mastering Elasticsearch 5.x : Master the intricacies of Elasticsearch 5 and use it to create flexible and scalable search solutions - Dixit, Bharvi (Birmingham, UK : Packt Publishing, 2017)
Master the intricacies of Elasticsearch 5 and use it to create flexible and scalable search solutions About This Book Master the searching, indexing, and aggregation features in ElasticSearch Improve users' search experience with Elasticsearch's functionalities and develop your own Elasticsearch plugins A comprehensive, step-by-step guide to master the intricacies of ElasticSearch with ease Who This Book Is For If you have some prior working experience with Elasticsearch and want to take your knowledge to the next level, this book will be the perfect resource for you.If you are a developer who wants to implement scalable search solutions with Elasticsearch, this book will also help you. Some basic knowledge of the query DSL and data indexing is required to make the best use of this book. What You Will Learn Understand Apache Lucene and Elasticsearch 5's design and architecture Use and configure the new and improved default text scoring mechanism in Apache Lucene 6 Know how to overcome the pitfalls while handling relational data in Elasticsearch Learn about choosing the right queries according to the use cases and master the scripting module including new default scripting language, painlessly Explore the right way of scaling production clusters to improve the performance of Elasticsearch Master the searching, indexing, and aggregation features in Elasticsearch Develop your own Elasticsearch plugins to extend the functionalities of Elasticsearch In Detail Elasticsearch is a modern, fast, distributed, scalable, fault tolerant, and open source search and analytics engine. Elasticsearch leverages the capabilities of Apache Lucene, and provides a new level of control over how you can index and search even huge sets of data. With this book you will finally be able to fully utilize the power that Elasticsearch. This book will give you a brief recap of the basics and also introduce you to the new features of Elasticsearch 5. We will guide you through the intermediate and advanced functionalities of Elasticsearch, such as querying, indexing, searching, and modifying data. We'll also explore advanced concepts, including aggregation, index control, sharding, replication, and clustering. We'll show you the modules of monitoring and administration available in Elasticsearch, and will also cover backup and recovery. You will get an understanding of how you can scale your ElasticSearch cluster to contextualize it and improve its performance. We'll also show ...
Description based on online resource; title from cover (Safari, viewed March 14, 2017).
Previous edition published: 2015.
Added to collection customer.56279.3
Keywords: Lucene (Electronic resource); Lucene (Electronic resource); Search engines -- Programming; Client/server computing -- Software; Querying (Computer science) -- Computer programs; Moteurs de recherche -- Programmation; Architecture client-serveur (Informatique) -- Logiciels; Bases de données -- Interrogation -- Logiciels; COMPUTERS / Databases / Data Warehousing; COMPUTERS / Databases / Servers; COMPUTERS / Data Processing; Search engines -- Programming; Client/server computing; Software